PENILAIAN KOMPETENSI GURU DI SD DELEGAN-2, SLEMAN, YOGYAKARTA - Sri Poerbowati; Retno Bayu (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Along with the development of education and also demands the competence of teachers, theassessment of teacher competence is a matter which is currently required, both by schools and society ingeneral. SD Delegan-2 is used as an example to assess teacher competence in this study. SD Delegan-2 islocated in Sleman, Yogyakarta province were rebuilt by the private sector due to the earthquake in 2007. Physical construction of the building by the private sector is also accompanied by an assessment of thecompetency of teachers who teach at the school. Collecting data in this study is using interviews and questionnaires. The data were analyzed descriptively. The minimum basic competence profile of teacherswho assessed include: planning of teaching, mastery of materials and teaching methods, and thedevelopment of teaching materials, the ability to establish relationships with students, and the ability toestablish a relationship with the environment. Based on the research results, the basic competence profileprimary teachers Delegan-2 included in both categories for planning instruction, mastery of materials andmethods of learning, and the ability to establish relationships with students. However, for the developmentof teaching materials, and the ability to establish a relationship with the environment, in the categoryenough.